2011
DOI: 10.1021/jf201120n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Pressure Processing on the Profile of Polyglutamyl 5-Methyltetrahydrofolate in Selected Vegetables

Abstract: In plants, folate occurs predominantly as 5-methyltetrahydrofolate (5MTHF) polyglutamyl forms. Differences in stability and bioavailability of food folate compared to synthetic folic acid have been attributed to the presence of the polyglutamyl chain. High-pressure processing (HPP) was tested for whether it might shorten polyglutamyl chains of 5MTHF species in fresh vegetables by enabling action of native γ-glutamylhydrolase (GGH). A validated ultrahigh-performance reversed-phase liquid chromatography–tandem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The endogenous enzyme, γ-glutamyl hydrolase, hydrolyses the polyglutamyl folates into the more bioavailable short-chain or monglutamyl folates during cell decompartmentalization. Once this enzyme is inactivated by different processes such as freezing usually preceded by blanching, keeping the long chain polyglutamyl folates causes reduction of bioavailability of folates [36]. Unlike freezing usually preceded by blanching, cell decompartmentalization without inactivation of the enzyme and facilitation of the hydrolysis of long chain polyglutamyl folates potentially improving their bioavailability is enabled by HP treatment [22].…”
Section: Bioaccesibility and Its Measurementmentioning
confidence: 99%
“…The endogenous enzyme, γ-glutamyl hydrolase, hydrolyses the polyglutamyl folates into the more bioavailable short-chain or monglutamyl folates during cell decompartmentalization. Once this enzyme is inactivated by different processes such as freezing usually preceded by blanching, keeping the long chain polyglutamyl folates causes reduction of bioavailability of folates [36]. Unlike freezing usually preceded by blanching, cell decompartmentalization without inactivation of the enzyme and facilitation of the hydrolysis of long chain polyglutamyl folates potentially improving their bioavailability is enabled by HP treatment [22].…”
Section: Bioaccesibility and Its Measurementmentioning
confidence: 99%
“…There are several studies about quantitative polyglutamyl folate profiles in vegetables (17,(20)(21)(22)(23)(24)(25)(26). An earlier study found pentaglutamyl and heptaglutamyl folate are the major forms in black beans while hexaglutamyl folate is the major form in the tomato fruit; however, the polyglutamyl folate forms in the alfalfa sprouts shift to short-chain forms such as monoglutamyl and tetraglutamyl forms (23).…”
Section: Pre-boiling Time Optimizationmentioning
confidence: 99%
“…The authors found a uniquely long 5-CH 3-H4PteGlun profile up to 17. 5-CH3-H4PteGlun in vegetables from different families has been profiled (17,19,21). The authors found 5-CH3-H4PteGlun in Brassicaceae is predominant as 5-CH3-H4PteGlu5 through 5-CH3-H4PteGlu7.…”
Section: Pre-boiling Time Optimizationmentioning
confidence: 99%
“…Almost the entire research focuses on the respective monoglutamates after enzymatic deconjugation of the polyglutamate vitamers [20,49,63]. Only a few studies focused on the polyglutamate distribution of mammalian tissue [64,65], bacteria [65] and raw vegetables [64,[66][67][68]. Yeast, however, has not been analyzed in terms of polyglutamate vitamers which typically account for the major occurring form in vivo.…”
Section: Introductionmentioning
confidence: 99%